Misleading DNA evidence : reasons for miscarriages of justice - Gill, Peter (Academic Press, 2014)
Misleading DNA Evidence: A Guide for Scientists, Judges, and Lawyers presents the reasons miscarriages of justice can occur when dealing with DNA, what the role of the forensic scientist is throughout the process, and how judges and lawyers can educate themselves about all of the possibilities to consider when dealing with cases that involve DNA evidence. DNA has become the gold standard by which a person can be placed at the scene of a crime, and the past decade has seen great advances in this powerful crime solving tool. But the statistics that analysts can attach to DNA evidence.